Complete genome sequence of Peptoclostridium difficile strain Z31. Issue 1 (December 2016) - Pereira, Felipe; Oliveira Júnior, Carlos; Silva, Rodrigo; Dorella, Fernanda; Carvalho, Alex; Almeida, Gabriel; Leal, Carlos; Lobato, Francisco; Figueiredo, Henrique
Abstract Background Peptoclostridium (Clostridium )difficile is a spore-forming bacterium responsible for nosocomial infections in humans. It is recognized as an important agent of diarrhea and colitis in several animal species and a possible zoonotic agent. Despite the known importance ofP. difficile infection in humans and animals, no vaccine or other effective measure to control the disease is commercially available. A possible alternative treatment forP. difficile infection is the use of a nontoxigenic strain ofP. difficile as a competitive exclusion agent. However, a thorough knowledge of this strain is necessary for this purpose. We selectedP. difficile Z31, a nontoxigenic strain (PCR ribotype 009), for investigation because it preventsP. difficile infection in a hamster model. Results The genome sequence ofP. difficile Z31 is a circular chromosome of 4298, 263 bp, with a 29.21 % GC content, encoding 4128 proteins, and containing 78 pseudogenes. This strain belongs to ST 3, clade 1, and has five phage regions in its genome. Genes responsible for resistance to tetracycline and erythromycin were detected and more importantly, Z31 also contains genes that promote spore production and stability, cell attachment, intestinal adherence, and biofilm formation. Conclusion In this study, we present the first complete genome sequence of nontoxigenicP. difficile strain Z31. When the Z31 genome was compared with those of other isolates available in GenBank, including a draft genome of a nontoxigenic strain, several unique regions were evident. Z31 contains no toxin genes, but encodes several non-toxin virulence factors, which may favor host colonization.